Performance analysis and mechanical determinants of the opening lap of the team sprint in elite-level track cycling - Kordi, M.; van Rijswijk, I. (European Journal of Sport Science, 2024)
The team sprint (TS) is a three-lap pursuit and the most revered event in track sprint cycling. The opening lap of the TS is an important determinant to the overall performance. But despite it being the most controlled and repeatable task in track sprint cycling, very little data are available to better understand the performance of the opening lap. The aim of this study was split into three-parts: part one, to better understand the profile and the indices thought to be determinants of the opening lap of the TS in elite sprint track cyclists. Part two of the study examined all available timing splits (15, 65, 125 and 250 m) from 36 standing-start laps. Part three of the study examined the peak torque outputs and peak power outputs of different various starts performed over a 3-month period. The results showed time to 125 m exhibited a near perfect relationship with starter lap performance. Very strong relationships were seen with 15 and 65 m split times and final lap performance. Peak torque of the lead starting leg and peak power output were shown to be highly predictive 15 m, 65 and 125 m performance in training. These data suggested the first 15 m is highly important and predicts a disproportionately high level of final opening lap time performance. Therefore, it is likely that peak power output normalised to system mass and peak torque of lead leg is a strong determinant of overall performance in the TS.